Establishment of optimise strategies in production of recombinant Hepatitis B surface antigen for chip-based antibody detection approach - Tam, Yew Joon (2015)
Hepatitis B surface antigen (HBsAg) antibody (anti-HBs) has shown to be an important serological marker in monitoring the success in hepatitis B vaccination. In this, the HBsAg protein plays a vital role as the basic component for anti-HBs detection assays due to its high reactivity and specificity. As such, the present thesis focuses on assessing and optimising key areas related to the downstream processing conditions specifically in the production of HBsAg from recombinant Pichia pastoris and in the establishment of chip-based anti-HBs detection prototype. A study of the Mut+ phenotype for the expression of recombinant hepatitis B surface antigen (HBsAg) in P. pastoris strain GS115 with a two-phase fed-batch protocol is described. Expression levels of HBsAg protein of 6.74 g/L Dry Cell Weight (DCW) and 26.07 mg/L of HBsAg concentration were achieved 48 h of expression. The use of the pPIC3.5K-HBsAg plasmid in the Mut+ phenotype enhanced the expression of HBsAg by a nearly 13 times higher volumetric productivity in the first 24 h and 35 times higher at peak production concentration. Comparison of AOX expression promoters relative to the HBsAg gene in the role of mRNA secondary structure during translation initiation revealed that HBsAg possesses lower folding stability with AOX1 Mut+ phenotype and was found better suited for HBsAg expression, which correlates with the ease of translation initiation under shake flask conditions. Subsequently, cell disruption strategies by high pressure homogenizer were optimized using response surface methodology (RSM) to correlate influencing factors affecting cell disruption capability and specific protein release of HBsAg from P. pastoris cells. From the results, an optimised cell disruption strategy with up-scale adaptability consisted of a number of passes set at 20 times, biomass concentration of 7.70 g/L of dry cell weight (DCW) and pulse pressure at 1,029 bar was demonstrated and was shown to increase cell disruption efficiency by 2- fold and 4-fold for specific protein release of HBsAg when compared to glass bead method yielding 75.68% cell disruption rate (CDR) and HBsAg concentration of 29.20 mg/L, respectively. Following the release of HBsAg from cell disruption, univariate screening approaches on factors affecting the purification performance of HBsAg on ion exchange chromatography (IEC) and size exclusion chromatography (SEC) techniques and the establishment of a two-step purification strategy were performed. The main results drawn showed that the IEC Q Sepharose XL column and optimum conditions of 4 mL sample loading volume, an elution buffer with 1.5 M NaCl concentration at pH 8 with an elution gradient length of 20 column volume and subsequent purification with SEC at a sample volume of 5 mL and a flow rate of 1 mL/min was able to efficiently purify HBsAg. An up-scaled version the established purification strategy comprising of the two techniques further demonstrated adaptability for scale-up operations with a final total PF of 94.82 ± 16.20, HBsAg purity of 95.48% and recovery yield of 78.07%. Finally, detection and quantification of anti-HBs using direct surface plasmon resonance (SPR) chip-based assay approach with recombinant HBsAg obtained as capturing agent was performed. Recombinant HBsAg derived from P. pastoris was immobilized under optimum binding conditions at a concentration of 150 mg/L, sodium acetate buffer at pH 4 and 0.6% Triton X-100 while effective regeneration of sensor surface was able to be done with 20 mM HCl. A dynamic range of detection from ~0.00098 to 0.25 mg/L was achieved and no cross-reactivity was found for the other known antibodies tested. Comparison of SPR chip-based assay with ELISA in terms of limit of detection generated an approximate 7-fold increase in sensitivity and a 2-fold increase in accuracy of the replicated results. The ability of the assay to detect anti-HBs in human sera samples was demonstrated with minor differences in comparison to that of the results obtained with ELISA.